ANALISIS POLA PEMILIHAN JALUR PENDAKIAN PENGUNJUNG DALAM MENDUKUNG BUSINESS INTELLIGENCE PARIWISATA - Mawar Pitri; Harma Oktafia Lingga Wijaya (UNIVED Press, 2026)
This study aims to analyze visitor behavior patterns in selecting hiking trails at Mount as a basis for decision-making driven by Business Intelligence (BI). The primary issue addressed is the congestion of hikers on specific trails, which risks ecological degradation and diminishes the quality of the tourism experience. This research employs two main methods: Market Basket Analysis (Association Rules) to map hikers' equipment needs based on their chosen trails, and Spatial Zoning Analysis to manage visitor density distribution in real-time.The results indicate a strong association between the